Clinical presentation and in-hospital outcomes of intraoperative red blood cell transfusion in non-anemic patients undergoing elective valve replacement - Zhou, Ren; Qian, Dewei; Li, Haiqing; Wang, Zhe; Shi, Sheng; Shen, Feng; Cheng, Lin; Yang, Dicheng; Yu, Min (Frontiers in Cardiovascular Medicine, 2022)
Background: Intraoperative transfusion is associated with adverse clinical outcomes in cardiac surgery. However, few studies have shown the impact of intraoperative red blood cell (RBC) transfusion on non-anemic patients undergoing cardiac surgery. We assessed the in-hospital clinical outcomes of non-anemic patients undergoing isolated valve replacements and investigated the predictors associated with intraoperative RBC transfusion. Methods: We enrolled 345 non-anemic patients undergoing isolated valve replacements in our department from January 2015 to December 2019. The patients were stratified by the receipt of intraoperative RBC transfusion. Baseline characteristics were compared between groups and multiple logistic regression was used to identify the predictors for intraoperative RBC transfusion. The association between intraoperative RBC transfusion and in-hospital outcomes was also evaluated. Results: Intraoperative RBC transfusion developed in 84 of the 345 enrolled patients (24.3%). Three independent predictors for intraoperative RBC transfusion of non-anemic patients undergoing isolated valve replacements were identified by multivariate logistic analysis, including female, iron deficiency and hemoglobin level. When the two groups were compared, a significant tendency of higher in-hospital mortality (6.0% vs. 1.1%, P = 0.033) and higher incidence of postoperative hypoxemia (9.5% vs. 2.7%, P = 0.007) were observed in the intraoperative RBC transfusion group. After adjustment, the presence of intraoperative RBC transfusion was associated with an increase in postoperative hypoxemia (OR = 3.36, 95% CI: 1.16-9.71, P = 0.026). Conclusions: Intraoperative RBC transfusion was associated with poorer clinical outcomes in non-anemic adults undergoing isolated valve replacements, which significantly increased the risk of postoperative hypoxemia. The independent predictors of intraoperative RBC transfusion, such as iron deficiency and female, were identified, which may be helpful for risk assessment and perioperative management.